Peculiarities of Prenatal Development of Lungs in Plain-Nosed (Vespertilionidae) and Horseschoe (Rhinolophidae) Bats - Kovalyova, I.M. (Вестник зоологии, 2002)
For the first time the prenatal development of lungs and their definitive structure were studied in representatives of plain-nosed bats (Vespertilionidae) and horseshoe bats (Rhinolophidae). The results of this investigation show that in the studied bats the laying of lungs being at the 14th stage of the embryogenesis, as well as their subsequent development right up to the 18th stage were of the same mode. However after the 18th stage the development of lungs in the studied plain-nosed bats was sharply different from that in horseshoe ones when forming the structure of these organs. The explanation of such a phenomenon is given in connection with distinctions in spatial reciprocal location of the thorax organs, the body, and the head during embryogenesis. The supposition about the probable mediated relation between the bats echolocation (namely methods of radiating signals) and the peculiarities of lungs structures was suggested. Впервые исследовано пренатальное развитие легких и их дефинитивное строение у представителей рукокрылых: гладконосых летучих мышей (Vespertilionidae) и подковоносых летучих мышей (Rhinolophidae). Установлено, что у исследованных рукокрылых, начиная с 14-й стадии эмбрионального развития, закладка легких, а также дальнейшее их развитие вплоть до 18-й стадии происходит одинаково. Однако после 18-й стадии развитие легких гладконосых и подковоносых летучих мышей резко различается в части структурообразования рассматриваемых органов. Объяснение обнаруженному феномену дается в связи с различиями в ходе эмбриогенеза пространственного взаиморасположения органов грудной полости, туловища и головы. Высказано предположение о возможной опосредованной связи эхолокации рукокрылых (а именно: способов излучения сигналов) с особенностями в строении легких.